The Late Paleozoic Tectonometamorphic Evolution of Patagonia Revisited: Insights From the Pressure‐ Temperature‐Deformation‐Time (P‐T‐D‐t) Path of the Gondwanide Basement of the North Patagonian Cordillera (Argentina) - Oriolo, Sebastián (2019)
Fil: Oriolo, Sebastián. CONICET‐Universidad de Buenos Aires. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires (IGEBA); Argentina.